Comparative analyses of two mathematical models obtained from two modeling techniques for prediction of compressive strength of sand-laterite blocks - Elizabeth, Okere Chinenye (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
Scheffe’s and Osadebe’s modeling techniques were used in formulating two mathematicalmodels for the prediction of compressive strength of sand laterite blocks. The models were testedfor adequacy using statistical tools. Comparative analyses were made on the results ofpredictions from the two models. The student’s t-test statistics proved that there is no significantdifference between the predicted results of the two models at an α-level of 0.5. The percentagedifference between the two model results ranges from a minimum of 0.25% to a maximum of6.66% which is also insignificant. These comparisons show that both models are adequate andany of them can be used for prediction of the compressive strength of sand -laterite blocks giventhe mix ratios or vice versa.